25-Hydroxyvitamin D status is associated with interleukin-6 methylation in adipose tissue from patients with colorectal cancer. Issue 20 (22nd September 2021) - Boughanem, Hatim; Ruiz-Limon, Patricia; Crujeiras, Ana B.; de Luque, Vanessa; Tinahones, Francisco J.; Macias-Gonzalez, Manuel
Abstract : A dysfunctional visceral adipose tissue (VAT) is characterized by increased production of proinflammatory cytokines, which may increase the risk of colorectal cancer (CRC). Abstract : A dysfunctional visceral adipose tissue (VAT) is characterized by increased production of proinflammatory cytokines, which may increase the risk of colorectal cancer (CRC). However, the epigenetic contribution to the inflammatory status is poorly understood. In our study, we hypothesized that a dysfunctional VAT may be a risk factor for CRC, through epigenetic modifications. Therefore, we aimed to study the transcriptional/methylation profile of proinflammatory cytokines and genes related to vitamin D metabolism in VAT from CRC patients, and evaluate their association with serum 25-hydroxyvitamin D (25(OH)D). We included 129 participants (68 healthy participants and 61 CRC patients). We found that the majority of the studied genes are upregulated and hypomethylated in CRC patients, when compared to the healthy subjects ( p < 0.05). In addition, serum 25(OH)D was associated with both mRNA gene expression and methylation of key genes, such as interleukin ( IL ) 6, IL10, vitamin D receptor ( VDR ) or cytochrome P450 subfamily 27 type B1 ( CYP27B1 ) ( p < 0.05). Interestingly, while high IL6 expression was related to poor survival in CRC ( p < 0.05), IL6 methylation was associated with an increased risk of CRC, in which 25(OH)D partially mediated this association ( p < 0.05). Our study suggests a potential association between epigenetic regulation of inflammatory mediators in VAT – such as IL6 – in the CRC context, in which 25(OH)D may mediate this risk. Therefore, vitamin D could affect the epigenetic status of IL6, which can be considered for additional preventive strategies.